2015
DOI: 10.6061/clinics/2015(08)09
|View full text |Cite
|
Sign up to set email alerts
|

Operative versus nonoperative treatment for displaced midshaft clavicle fractures: a meta-analysis based on current evidence

Abstract: Literature searches of the Cochrane Library, PubMed, EMBASE, Web of Science, LILACS, China National Knowledge Infrastructure, and Wanfang Data databases were performed from 1966 to September 2014. Only randomized and quasi-randomized controlled clinical trials comparing operative and nonoperative treatments for displaced midshaft clavicle fractures were included. Data collection and extraction, quality assessment, and data analyses were performed according to the Cochrane standards. Thirteen studies were consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 46 publications
2
38
0
7
Order By: Relevance
“…They have concluded that operative treatment is superior to nonoperative treatment in the management of displaced midshaft clavicle fractures. 16 In our study we did not encounter any neurological complication, which may support their finding.…”
Section: Discussionsupporting
confidence: 86%
“…They have concluded that operative treatment is superior to nonoperative treatment in the management of displaced midshaft clavicle fractures. 16 In our study we did not encounter any neurological complication, which may support their finding.…”
Section: Discussionsupporting
confidence: 86%
“…Most midshaft clavicle fractures are displaced, as a result of the muscular action and the weight of the arm [ 6 , 8 ]. Treatment of displaced midshaft clavicle fractures is still controversial [ 10 , 11 , 12 , 13 , 14 , 15 ]. Traditionally, these fractures have been treated nonoperatively, even in cases of severe displacement or comminution, based on the high capacity of healing and remodeling of the clavicle [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of a misleading X-ray is either malunion of the clavicle in conservative treatment, which can lead to shoulder complaints or unexpected finding during surgery, which can complicate the operation. 4 Due to the risk of non-union and the young age of the patient an operation was planned. Although this type of fracture (and the operative possibilities) is already described by Neer in 1963, till this date there is no universally agreed standard operative procedure for displaced distal clavicle fractures.…”
Section: Relevant Literature/discussionmentioning
confidence: 99%